Exploring chest wall deformities in childhood and adolescence: insights from a case-control study - Fedli Emre Kılıç; Osman Küçükkelepçe; Celal Varan; Hüseyin Tanrıverdi; Furkan Bakırhan (BMC, 2024)
Abstract Background Chest wall deformities, though relatively uncommon in childhood and adolescence, significantly affect aesthetic perception and can impact cardiac and respiratory function. This study aims to compare individuals with pectus deformities to a healthy control group, shedding light on the condition's etiology and prognosis. Method Conducted as a case-control study between 2020 and 2022, the research included a case group of 71 patients with pectus excavatum or pectus carinatum who were followed up at the Pediatric Cardiology outpatient clinic. The control group consisted of 80 children without chronic diseases. Researchers retrospectively reviewed patient files, recording demographic data, echocardiography findings, and serum levels of calcium, phosphate, vitamin D, and alkaline phosphatase. Results Patients with chest wall deformities exhibited significantly lower serum levels of vitamin D, calcium, and phosphorus compared to those without deformities. Males constituted 77% of the case group, with 15.5% exhibiting abnormal echocardiogram results, with mitral valve anomalies being most prevalent. Conclusion While pectus deformities may lead to cardiac or respiratory issues, patient concerns often center around aesthetics. Unlike typical studies focused on surgical techniques and postoperative patients, our study focused on all diagnosed patients. Findings emphasize the importance of monitoring calcium, phosphorus, and vitamin D levels in pectus patients to manage surgical risks and facilitate recovery.